Should nucleotide sequence analyzing computer algorithms always extend homologies by extending homologies? - Burnett, L (1986)
Most computer algorithms used for comparing or aligning nucleotide sequences rely on the premise that the best way to extend a homology between the two sequences is to select a match rather than a mismatch. We have tested this assumption and found that it is not always valid.